Growth That Starts from Thinking - Roosevelt, Eleanor (Tufts Archival Research Center, 2006)
Eleanor Roosevelt describes growing up in a religious household and later questioning her childhood beliefs, and concludes with the belief that a person must simply do the best that she can while meeting the future with courage.